APLIKASI MEDIA BANTU PEMBELAJARAN KRIPTOGRAFI DENGAN MENGGUNAKAN ALGORITMA MESSAGE DIGEST 5 (MD5) - Zein Zein; Ahmat Adil (Universitas Bumigora, 2016)
College of Informatics and Computer Management (STMIK) Bumigora Mataram, for Computer Network competencies are elective courses that network security system which addresses the cryptographic material using a lecture and power point as a medium while studying in the classroom. Those problems led to the idea to create teaching aids media applications using cryptographic message digest algorithm 5 (MD5). Cryptography is the science that is used to encrypt a message, so the message private. On the application every student can learn and try to direct the activities of the MD5 algorithm program in step by step. This algorithm has a characteristic that the message is converted into a message digest can not be restored into the original message. Two different messages always produce different hash values. So as to facilitate faculty to improve student comprehension. Based on the results of questionnaires to the lecturer stated that the application can assist the lecturer delivered material MD5 cryptographic algorithm. And the results of the questionnaire of the student that can be assisted in doing to learn anytime and anywhere as long as the application can access media learning aids such as web-based applications online.